Mergers and acquisitions : the pharmaceutical and biotechnology industries - Thomas, Mark (Writer on mergers); Rose, Janna (Routledge, 2024)
"Covid-19 has brought so much uncertainty, but one certainty is that the vaccine race will generate winners and losers in the pharmaceutical and biotechnology industries. This will have a major impact on merger and acquisition activity. While the plethora of merger and acquisition deals are abundantly reported by the news media, there is a clear lack of in-depth analysis on the multiple rationales and various challenges in the life sciences industry. By offering contributions from a variety of experts in the biotechnology and pharmaceutical industries, as well as experts on mergers and acquisitions, this edited collection will draw upon the knowledge of a variety of different actors within the fields of pharma and biotech. This book offers a timely exploration of the complexities of mergers and acquisitions in the pharmaceutical and biotechnology industries while seeking to bridge the gap between theory and practice. It presents a critical analysis of the rationale for acquisitions and studies the challenges of ensuring a successful deal. In the light of the Covid-19 pandemic, it will also explore the impact this may have on the industry, which may further stimulate mergers and acquisitions activity. It will be of interest to researchers, academics, policymakers, and students in the fields of strategy, management, governance, and the biotechnology and pharmaceutical industries"-- Provided by publisher.
Keywords: Pharmaceutical industry -- Mergers.; Biotechnology industries -- Mergers.; elektronické knihy; electronic books